2010
DOI: 10.1080/0092623x.2010.488113
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of “Big Decisions”: An Abstinence-Plus Sexuality Curriculum

Abstract: This study examines the effectiveness of Big Decisions, a sexuality curriculum developed to promote abstinence, as well as condom and contraceptive use, while overcoming school districts' concern about controversy surrounding sex education. The authors used a pre- and post-test survey design to measure changes in attitudes, self-efficacy, and behavioral intentions regarding sex, pregnancy, sexually transmitted diseases, and condom use. The sample for this analysis included 788 inner-city 9th-grade students, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…These differences between abstinence-only and abstinence-plus students' scores are not surprising because although both programs teach abstinence, abstinence-plus programs also included material on pregnancy, HIV, STIs, and contraceptives (Masters et al, 2008). Furthermore, several previous studies (Kirby, 2008;Lindberg & Maddow-Zimet, 2012;Masters et al 2008;Realini et al, 2010) have reported results that were consistent with the current findings.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These differences between abstinence-only and abstinence-plus students' scores are not surprising because although both programs teach abstinence, abstinence-plus programs also included material on pregnancy, HIV, STIs, and contraceptives (Masters et al, 2008). Furthermore, several previous studies (Kirby, 2008;Lindberg & Maddow-Zimet, 2012;Masters et al 2008;Realini et al, 2010) have reported results that were consistent with the current findings.…”
Section: Discussionsupporting
confidence: 87%
“…Several researchers have studied the influence of abstinence-plus programs on teenagers' sexual health and some studies on the effectiveness of these programs have shown some positive results (Kirby, 2008;Kohler, Manhart, & Lafferty, 2008;Realini et al, 2010). Abstinence-plus advocates report that these programs can delay teenagers' initiation of sexual activities and increase contraceptive use (Kirby, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, to address high prevalence of sexual activity and early initiation, a sexual education program (adapted Big Decisions®, [34]) is being introduced in the middle and high schools in these communities. The southwest Trifinio schools historically have had no reproductive and sexual health curriculum despite the national policy agreement by the Ministry of Education that introduced the Integrated Strategy of Sexual Education and Violence Prevention in 2010.…”
Section: Discussionmentioning
confidence: 99%
“…In sum, this study identifies message strategies used by emerging adults to abstain from or delay sexual intercourse and shows the outcomes of those strategies. The communicative actions employed during these interactions can be included in intervention programs, aimed at encouraging abstinence or safe sex practices (Realini, Buzi, Smith, & Martinez, 2010).…”
Section: Limitations and Future Researchmentioning
confidence: 99%